Proses Kreativitas dan Apresiasi Seni Dalam Pembelajaran Seni Tari Bagi Mahasiswa PIAUD UIN Sunan Ampel Surabaya - Lisa Alistiana (Program Studi PGMI STAI Daruttaqwa Gresik, 2020)
This study aims to develop creativity and appreciation of art in learning dance for students of UIN Sunan Ampel Surabaya PIAUD. Learning dance is very useful for PIAUD students because it can improve the ability to learn dance in art appreciation activities. Creativity in this research is to create a new thing in individual learning. In general, creativity and appreciation lead to the process of moving that drives someone in an action. Desires that must continue to be fostered for the process of learning dance one of them with a form of appreciation, because in the form of appreciation of art contains a beauty or aesthetic dance moves, as well as expression in learning dance know that dance creation also contains a beauty. The process of dance work will be an aesthetic experience for students who are in line with their educational interests through learning dance. This process is carried out continuously so that the appreciation of PIAUD students towards dance as expected and will increase and have creativity towards learning dance when they become kindergarten teachers.